Advanced Ovarian Dysgerminoma Infiltrating Both Ovaries and Uterus in a 7-Year-Old Girl - Nexhmi Hyseni; Sadik Llullaku; Hysni Jashari; Kaltrina Zahiti; Fjolla Hyseni; Fisnik Kurshumliu; Lumturije Luci; Fehim Muqolli; Antigona Hasani (Case Reports in Oncological Medicine)
Introduction. Ovarian dysgerminoma is a rare malignant ovarian germ cell tumor with its peak incidence in young women. Abdominal pain, abdominal distention, and the presence of a palpable mass are common symptoms at presentation. Depending on the FIGO stage at presentation the prognosis of dysgerminomas after surgical treatment, adjuvant chemotherapy, and radiotherapy is promising. Case Presentation. A 7-year-old girl was presented at our clinic with abdominal pain in all abdominal quadrants. Later the pain localized in the region of her right ovary. CT scan revealed a massive formation which was connected to her right ovary. Conclusion. Although malignant ovarian germ cell tumours are rare in children, physicians must always consider the possibility of MOGT-occurrences. The clinical symptoms might not be specific: abdominal pain, abdominal distention, nausea, and vomiting. In order to make a correct diagnosis the patients should undergo a complete clinical examination including radiological scans. Initial management is frequently surgery, followed by adjuvant chemotherapy and radiotherapy. Although disgerminoma is malignant tumor, the prognosis is promising.